Contact force guided radiofrequency current application at developing myocardium. (28th May 2022) - Backhoff, David; Müller, Matthias J.; Betz, Teresa; Arnold, Andreas; Schneider, Heike; Paul, Thomas; Krause, Ulrich
Abstract: Introduction: Catheter contact is a key determinant for lesion size in radiofrequency catheter ablation (RFA). Monitoring of contact force (CF) during RFA has been shown to improve efficacy of RFA in experimental settings as well as in adult patients. Coronary artery narrowing after RFA has been described in experimental settings as well as in children and adults and may be dependent from catheter contact. The value of CF monitoring concerning these issues has not been systematically studied yet. Value of high versus low CF during RFA in piglets was studied to assess lesion size and potential coronary artery involvement mimicking RFA in small children. Methods: RFA with continuous CF monitoring was performed in 24 piglets (median weight 18.5 kg) using a 7 F TactiCath Quartz radiofrequency (RF) ablation catheter (Abbott). A total of 7 lesions were induced in each animal applying low (10−20 g) or high (40−60 g) CF. RF energy was delivered with a target temperature of 65°C at 30 W for 30 s. Coronary angiography was performed prior and immediately after RF application. Animals were assigned to repeat coronary angiography followed by heart removal after 48 h ( n  = 12) or 6 months ( n  = 12). Lesions with surrounding myocardium were excised, fixated, and stained. Lesion volumes were measured by microscopic planimetry. Results: A total of 148 RF lesions were identified in the explanted hearts. Only in the subset of lesions at the AV annulus 6 month after ablation, lesion size and number of lesions exhibiting transmural extension were higher in the high CF group compared to low CF. In all other locations CF had no impact on lesion size and mural extension after 48 h as well as after 6 months. Additional parameters such as lesion size index and force time integral were also not related to lesion size. Coronary artery damage was present in two animals after 48 h and in one after 6 months and was not related to CF. Conclusion: In our experimental setting, lesion size in piglets was not related to catheter CF. Transmural extension of the RF lesions involving the layers of the coronary arteries was frequently noted irrespective of CF. Coronary artery narrowing was present in 3/24 animals and was not related to CF. In infants and toddlers, low CF (10−20 g) may be of adequate effect. Impact of CF monitoring during conventional RF ablation in children requires further investigation.